The Effectiveness of Using Self Instruction in Increasing Low Self-Esteem in Late Adolescence - Ismah, Fildzah Azatil; Widayat, Iwan Wahyu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Self esteem is one of the crucial aspects in the lives of adolescents. This is because during adolescence, individuals can recognize and develop various aspects within themselves, enabling them to determine whether they fall into the category pf positive or negative self esteem. Individuals with high self-esteem tend to have lead happier and more productive lives. Meanwhile, those with low self-esteem have negative perceptions when evaluating themselves and their surroundings. If self esteem issues in adolescents are not promptly addressed, they can have long term consequences on their overall development. Therefore, self esteem is considered significant, necessitating efforts to enhance it. One intervention that can be applied to boost self esteem is the utilization of the self instruction method. The aim of this research is to evaluate the extent of the success of the self instruction method in improving self esteem in late adolescents. The subjects are late adolescents, 19 years old, female, and currently attending high school. The measurement of self-esteem utilizes two scale the Rosenberg Self-Esteem Scale (RSES) and Coopersmith Self-Esteem Inventory (CSEI). In addition to administering the scales, observations, interviews, graphic tests, SSCT, and 16 Pf are conducted. The intervention involves individual self instruction method includes for main steps proposed by Meichenbaum. The experimental design in this research employes an A-B approach in a single-case experimental design pattern. The results indicate that the intervention using the self instruction method effectively raises the self-esteem of subject.Self esteem merupakan salah satu aspek penting pada diri remaja. Hal tersebut disebabkan pada masa remaja individu dapat mengenali dan mengembangkan aspek apa saja yang ada dalam dirinya, sehingga remaja mampu menentukan apakah ia masuk dalam kategori self esteem positif ataukah self esteem negatif. Individu dengan self esteem tinggi akan menjalani hidupnya dengan bahagia dan lebih produktif. Sementara itu individu dengan self esteem rendah memiliki persepsi negatif dalam menilai diri dan lingkungan. Apabila permasalahan self esteem pada remaja tidak segera ditangani akan berdampak pada masa perkembangan selanjutnya. Maka dari itu self esteem dianggap cukup penting, sehingga perlu adanya usaha dalam meningkatkan self esteem. Salah satu intervensi yang dapat diterapkan untuk menaikkan self esteem adalah memanfaatkan metode self instruction. Tujuan dari penelitian ini adalah mengevaluasi sejauh mana keberhasilan metode self instruction dalam manaikkan self esteem pada remaja akhir. Subjek merupakan remaja akhir dengan usia 19 tahun, berjenis kelamin perempuan dan sedang duduk dibangku SMA. Pengukuran dalam melihat self esteem menggunakan dua skala yaitu Rosenberg self Esteem Scale (RSES) dan Coopersmith Self Esteem Inventory (CSEI). Selain pemberian skala dilakukan juga observasi, wawancara, tes grafis, SSCT, dan 16 Pf. Tindakan intervensi yang diterapkan melibatkan penanganan individual pada subjek dengan memanfaatkan metode self instruction. Metode self instruction yang diimplementasikan melibatkan 4 langkah yang diajukan oleh Meichenbaum. Desain eksperimental pada penelitian ini menggunakan pendekatan A-B dalam pola single case experimental design. Hasil penelitian mengindikasikan bahwa intervensi menggunakan metode self instruction efektif menaikkan self esteem pada subjek.